Enhancing reindeer husbandry in boreal Sweden - Berg, Staffan; Lind, Torgny; Valinger, Erik (Zenodo, 2017)
The use of a GPS tracking system has led to a change in the labour process of reindeer husbandry, as the herd can be monitored and followed remotely on computers. It increases knowledge about migrationroutes and use of grazing areas as themovements are registered by the trackingdevices. With the aid of the GPS trackingsystem, vehicle mileage could be reducedand predator attacks on the herd can bedetected at an early stage. These attacksare a very serious concern for Sami herdsmen due to economic losses.